Manajemen Penyelesaian Konflik dalam Peningkatan Kinerja Guru di Pondok Pesantren Al-Ihsan Pandeglang - Saputra, Ales; MS, Farizal; Tanrere, Syamsul Bahri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze conflict management at Pondok Pesantren Al-Ihsan Pandeglang, focusing on improving teacher performance and the leadership style of the pesantren. The method used is qualitative research with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving teachers, students, and pesantren leaders. Data analysis was conducted descriptively using a triangulation approach to ensure the validity and reliability of the data. The results show that teacher performance at Pondok Pesantren Al-Ihsan is significantly influenced by internal factors such as competence, responsibility, and work ethic, as well as external factors such as interpersonal relationships, communication, and reward systems. Most conflicts within the pesantren environment stem from differences in perspectives, lack of coordination, and unclear task distribution. To address these issues, a leadership style based on deliberation and a collaborative approach has proven effective in resolving conflicts. This research provides significant implications for pesantren management, particularly in strengthening conflict management systems through improving teacher performance and developing an inclusive and solution-oriented leadership style. By implementing appropriate strategies, Pondok Pesantren Al-Ihsan can create a harmonious, productive learning environment that supports the character development of students.